Factors That Determine the Prothrombin Time in Patients With Atrial Fibrillation Receiving Rivaroxaban. (December 2018) - Huang, Jen-Hung; Lin, Yung-Kuo; Chung, Cheng-Chih; Hsieh, Ming-Hsiung; Chiu, Wan-Chun; Chen, Yi-Jen
Rivaroxaban, a direct factor Xa inhibitor, is widely used to reduce the chance of stroke in patients with atrial fibrillation (AF). It is not clear why the prothrombin time (PT) of the international normalized ratio (INR) fails to correlate with treatment using rivaroxaban in patients with AF. In this study, patient characteristics, the rivaroxaban dosage, AF type, drug history, biochemical properties, and hematological profiles were assessed in patients treated with rivaroxaban. In 69 patients with AF receiving rivaroxaban, 27 (39.1%) patients had a normal INR (≤1.1, group 1), 27 (39.1%) patients had a slightly prolonged INR (1.1∼1.5, group 2), and 15 (21.7%) patients had a significantly prolonged INR (>1.5, group 3). Group 1 patients had a higher incidence of a stroke history than did patients in group 2 ( P = .026) and group 3 ( P = .032). We scored patients with a persistent AF pattern (1 point), paroxysmal AF pattern (0 point), renal function (ie, the creatinine clearance rate in mL/min/1.73 m 2 of >60 as 0 points, of 30∼60 as 1 point, and of <30 as 2 points), and no history of stroke (1 point), and we found that group 3 had a higher score than groups 2 or 1 (2.9 ± 0.8, 2.4 ± 0.7, and 2 ± 0.7, respectively; P < .05). There were similar incidences of bleeding, stroke, and unexpected hospitalizations among the 3 groups. The PT of the INR is determined by multiple variables in patients with AF receiving rivaroxaban. Rivaroxaban-treated patients with AF having different INR values may have similar clinical outcomes.